Structural characterization of diastereoisomeric ethano adducts derived from the reaction of 2'-deoxyguanosine with trans,trans-2,4-decadienal - Loureiro, APM; Campos, IPD; Gomes, O. F.; Di Mascio, P.; Medeiros, MHG (Amer Chemical Soc, 2004)
Background levels of exocyclic DNA adducts have been detected in rodent and human tissues. Several studies have focused on bifunctional electrophiles generated from lipid peroxidation as one of the endogenous sources of these lesions. We have previously shown that the reaction of 2'-deoxyguanosine (dGuo) with trans,trans-2,4-decadienal (DDE), a highly cytotoxic aldehyde generated as a product of lipid peroxidation in cell membranes, results in the formation of a number of different base derivatives. Three of these derivatives have been fully characterized as 1,N-2-etheno-2'-deoxyguanosine adducts. In the present work, four additional adducts, designated A3-A6, were isolated from in vitro reactions by reversed-phase HPLC and fully characterized on the basis of spectroscopic measurements. Adducts A3-A6 are four diastereoisomeric 1,N-2-hydroxyethano-2'-deoxyguanosine derivatives possessing a carbon side chain with a double bond and a hydroxyl group. The systematic name of these adducts is 6-hydroxy3-(2'-deoxy-beta-D-erythro-pentafuranosyl)-7-((E)-1-hydroxy-oct-2-enyl)-3,5,6,7-tetrahydro-imidazo- [1,2-a]purin-9-one. The proposed reaction mechanism yielding adducts A3-A6 involves DDE epoxidation at C2, followed by nucleophilic addition of the exocyclic amino group of dGuo to the C1 of the aldehyde and cyclization, via nucleophilic attack, on the C2 epoxy group by N-1. The formation of adducts A1-A6 has been investigated in acidic, neutral, and basic pH in the presence of H2O2 or tent-butyl hydroperoxide. Neutral conditions, in the presence of H2O2, have favored the formation of adducts A1 and A2, with minor amounts of A3-A6, which were prevalent under basic conditions. These data indicate that DDE can modify DNA bases through different oxidative pathways involving its two double bonds. It is important to structurally characterize DNA base derivatives induced by alpha,beta-unsaturated aldehydes so that the genotoxic risks associated with the lipid peroxidation process can be assessed.